Corps, ethos et communication. Hommage à Charles Perraton - Charles Perraton; Fabien Dumais (Communiquer)
This article draws a meaningful portrait of Charles Perraton, a recently retired professor at Département de communication sociale et publique (UQAM). It includes an interview with the professor as well as some testimonies made by colleagues and students under his mentorship. Numerous themes are covered including his encounters with renowned intellectuals, his approach to mentoring students, his university careers, his teaching methods, some theoretical diagonals extracted from his articles, and finally, the ethical modalities that he continues to follow. In his attempts to act with dignity in the tumultuous uncertainty of life, he experiments with joy and various communicative paths of transformation.